UPAYA PASANGAN SUAMI-ISTRI PENYANDANG DISABILITAS DALAM MEMBENTUK KELUARGA SAKINAH PERSPEKTIF PSIKOLOGI KELUARGA - Daud, Fathonah K.; Baroroh, Nunuk Umi; Akbar, Zainuri (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2025)
This research examines several efforts of husband and wife couples with disabilities in forming a sakinah family from a family psychology perspective. The aim of this research is to find out several efforts and things that are factors in the formation of sakinah families as well as factors that hinder sakinah families in families of people with disabilities. This research is descriptive qualitative in nature, with data collection methods carried out by means of observation, interviews and documentation. The objects of this research are residents of Sokogrenjeng Kenduruan Tuban village who have disabilities and have partners. This is not easy to achieve, because disabled couples certainly have many obstacles in achieving this. The research results show that there are several efforts to create a sakinah family, including harmony in the family, responsibility between husband and wife, ideal leaders, support from family and the environment, based on a sense of mawaddah and mercy. Apart from that, there are several efforts specifically for psychological needs that are implemented to create a sakinah family, including strong cohesion, accepting agreements within the family, a sense of belonging, good communication, a sense of attraction between family members, and each member trying to achieve family goals. . This shows that family psychology has an important role in the family to achieve a harmonious family for couples with disabilities. This research makes an important contribution to our understanding of efforts to form a sakinah family, especially for couples with disabilities, that it is not easy to create a sakinah family, especially in limited conditions.